Do Welfare States Reduce Poverty? A Critical Shortcoming in the Standard Analysis of the Anti-Poverty Effect of Welfare States - Hwanjoon Kim (Luxembourg Income Study (LIS), 2000)
A standard analysis of the anti-poverty effect of taxes and income transfers is to compare pre-tax-transfer poverty and post-tax-transfer poverty. A critical shortcoming of the standard approach is that it treats pre-tax-transfer poverty as given and ignores potential effects of taxes and transfers on pre-tax-transfer poverty. Using cross-national variation, this study examines potential endogeniety of pre-tax-transfer poverty. The results suggest that both the generosity and efficiency of the tax/transfer system may influence the level of pre-tax-transfer poverty. If this is true, the standard approach overestimates the anti-poverty effectiveness of generous and/or targeted welfare systems.
Keywords: 330; Einkommensumverteilung; Steuerpolitik; Öffentliche Sozialleistungen; Armutsbekämpfung; Sozialstaat; Industrieländer